Exiting from Lockdowns : Early Evidence from Reopenings in Europe - Franks, Jeffrey (IMF Working Papers; Working Paper, 2020)
European authorities introduced stringent lockdown measures in early 2020 to reduce the transmission of COVID-19. As the first wave of infection curves flattened and the outbreak appeared controlled, most countries started to reopen their economies albeit using diverse strategies. This paper introduces a novel daily database of sectoral reopening measures in Europe during the first-wave and documents that country plans differed significantly in terms of timing, pace, and sequencing of sectoral reopening measures. We then show that reopenings led to a recovery in mobility-a proxy for economic activity-but at the cost of somewhat higher infections. However, the experience with reopening reveals some original dimensions of this trade-off. First, the increase in COVID-19 infections after reopening appears less severe in fatality rates. Second, a given reopening step is associated with a worse reinfection outcome in countries that started reopening earlier on the infection curve or that opened all sectors at a fast pace in a relatively short time. Finally, while opening measures tend to have an amplification effect on subsequent cases when a large fraction of the economy is already open, this effect appears heterogenous across sectors.